THE IMPLEMENTATION OF COMMUNICATIVE LANGUAGE TEACHING (CLT) METHOD THROUGH PLAYFUL ENGLISH APPROACH TO IMPROVE STUDENTS' SPEAKING SKILLS AT PKBM PESONA PULAU TEGAL - Saputri, Vike Aprilianin Marwintaria; Andriyaningsih, Ayu; Kusuma, Candra (PT. Jurnal Center Indonesia Publisher, 2025)
The ability to speak English is very important, especially for coastal communities such as those on Tegal Island, which has tourism potential. However, students at the Pesona Pulau Tegal Community Learning Center (PKBM) still have difficulty communicating, especially in English, because learning has tended to be conventional, focusing on memorization and grammar rather than practical communication. This creates a gap between the need for speaking skills and the teaching methods used, reinforcing students' fear and lack of confidence. Based on these issues, this Community Service activity aims to improve students' speaking skills through the application of the Communicative Language Teaching (CLT) method integrated with the Playful English approach, which involves enjoyable learning through games, role-play, and creative activities. The methods used include guided speaking exercises, conversation simulations, and collaborative projects such as creating promotional posters for beach tourism in English. The results show a significant improvement in students' fluency, confidence, and active participation. Students began to speak more boldly, practice simple sentences, and express ideas spontaneously. The classroom atmosphere became livelier and more enjoyable with minimal psychological barriers such as fear of making mistakes. The implications of this activity are that the CLT approach combined with elements of joy can serve as an effective learning model in non-formal institutions. This method not only enhances language skills but also empowers students socially and emotionally, and can be replicated in similar communities.